New head gradient coil design and construction techniques. Issue 5 (9th October 2013) - Handler, William B.; Harris, Chad T.; Scholl, Timothy J.; Parker, Dennis L.; Goodrich, K. Craig; Dalrymple, Brian; Van, Frank; Chronik, Blaine A.
<x xml:space="preserve">Abstract</x> Purpose To design and build a head insert gradient coil to use in conjunction with body gradients for superior imaging. Materials and Methods The use of the boundary element method to solve for a gradient coil wire pattern on an arbitrary surface allowed us to incorporate engineering changes into the electromagnetic design of a gradient coil directly. Improved wire pattern design was combined with robust manufacturing techniques and novel cooling methods. Results The finished coil had an efficiency of 0.15 mT/m/A in all three axes and allowed the imaging region to extend across the entire head and upper part of the neck. Conclusion The ability to adapt an electromagnetic design to necessary changes from an engineering perspective leads to superior coil performance. J. Magn. Reson. Imaging 2014;39:1088–1095. © 2013 Wiley Periodicals, Inc.